Apis florea drone flight: Longevity and flight performance - Ninat Buawangpang (2018)
Mating flight records are presented for males (drones) of the Asian dwarf honeybee species Apis florea. These include observations on longevity, mortality and inclusive flight records for a cohort of known-aged males. Averages for flight performance show the flights/lifetime to be 15.3 (± 11.8 SD); the number of flight days, 9.1 (± 6.5 SD) and a drone mating flight lasting ca. 31 min (± 9 min, 27 s SD). For a smaller group of known-aged males, for which complete daily flight performance was recorded for all days of flight, the mean summed flight time was 6 h 38 min (± 5 h 53 min SD). Longevity and mortality data show the average age for commencement of flight to be 5.6 days (± 1.3 SD) and the mean age for the final flight to be 15.6 days (± 9.2 SD), providing an average reproductive flight window of 10 days. These observations for A. florea male longevity and mortality are significantly shorter than those reported for the western honeybee (Apis mellifera L.) as observed in temperate climates of North America. © INRA.